Effects of Sustained Deficit Irrigation on Vegetative Growth and Yield of Plum Trees Under the Semi-Arid Conditions: Experiments and Review with Bibliometric Analysis - Laita, Meriame; Sabbahi, Rachid; Elbouzidi, Amine; Hammouti, Belkheir; Messaoudi, Zerhoune; Benkirane, Rachid; Aithaddou, Houssain (Universitas Pendidikan Indonesia (UPI), 2024)
This study evaluated sustained deficit irrigation on the production and quality of plum trees under the semi-arid conditions of the Saïs plain, with four water regimes: T0 (dose practiced by the farmer which may be equal to or greater than 100% ETc), T1 (100% ETc), T2 (80%ETc) and T3 (60%ETc) during the agricultural year 2017/2018. The results of the study showed a significant influence of the irrigation dose on vegetative parameters such as shoot diameter and length, physiological parameters such as leaf temperature, production parameters such as fruit yield per tree and fruit number per tree, and quality parameters such as acidity and sugar content. The fruits grown on T3 (60 %ETc)-treated trees had the highest sugar content. The total acidity of the fruit juice decreased with the increase in sugar content. In summary, the main parameters of vegetative growth, production, and quality were significantly affected by the reduction in irrigation dose. The findings also suggested that a 20% reduction in irrigation dose is feasible without significantly affecting the yield. A bibliometric analysis is conducted on the collected papers on Scopus on sustainable deficit irrigation and its impact on vegetative growth from 1999 to 2023.